Design forward: biomimicry approach in sustainable landscape ecology - Idrus, Nur Afikah; Mohd Yunos, Mohd Yazid; Ismail, Nor Atiah (Universiti Kuala Lumpur Publishing, 2016)
The density of human population in an urban area of this era increases strongly. Its at risk as the capacity continues critically at the alarming rate even though the city nowadays is in unsustainable behaviour challenge of majority come from landscape ecology. This scenario is mostly cases of the implementation sustainability-oriented contemporary urban planning and relationship between landscape ecological design practices. The most difficult problem is in enhancing the urban ecological area in various perspectives of developing future patterns and theories although it relevant for socio-economic issues, environmental concerns and context of planning. However, this paper examines the application of biomimicry in sustainable landscape ecology and obtains the lesson beyond the formalistic characteristic design to more responsive understanding nature. Besides, it generates significant to explore sustainable and relevant solution towards design form and approach for successful landscape ecology. Biomimicry is an expression of imitation of the life process in nature reveals the unsustainable behaviour as the design field seen to imitate nature. Therefore, a qualitative method research is involved by having comprehensive content analysis throughout different task of ideas to strengthen the design context and interpreted the existing design instead of new design. Nevertheless, within the design context strikingly identify the biomimicry approach and develop multi-disciplinary design framework by having nature as inspiration to the future design field. The expected added value of integrating biomimicry approach into sustainable landscape ecology may be improved on social life behaviour which is more responsive towards natural environmental setting, economic, political issues and most importantly changing urban thought and understanding the fundamental approach of biomimicry that leads the globe objectives for enhancing the sustainable landscape ecology development. Thus, this study highlight that biomimicry approach as the emerging trends and opportunities areas by moving ahead of the transfer and sharing knowledge between the designers and biologist.